Mechanism in damage variation of nanosecond laser-induced damage of germanium sheets in vacuum. (January 2023) - Liu, Gangshuo; Kuang, Dengfeng; Song, Lipei; Xu, Can; Yan, Chao
Highlights: Surface degradation of Ge in vacuum on different laser conditions are showed. The influences of processing parameter and material failure behavior are analyzed. Mechanism in damage variation with laser ablation is compared in air and vacuum. Damage mechanism contains thermal effect, plasma shock wave and mechanical stress. Abstract: Laser-induced damage of germanium (Ge) sheets plays a key role to estimate the lifetime of optical components in the vacuum and space irradiation environment. However, the dependence between the degrees of laser-induced surface damage and nanosecond pulsed irradiation remains unclear for Ge sheet. Here, we investigate damage morphology and the growth characteristic of Ge sheets under different conditions and measure the laser-induced damage threshold (LIDT) in vacuum. Our results reveal that optical reflectivity of Ge in vacuum chamber falls 92% because of the defective sites on the damaged surface. The area, the depth and the size of the damage crater increase but the hillock height and the surrounding thermal diffuse area decrease along with the increase of vacuum degree. The thermal effect, the failure effect of plasma shock wave and the mechanical stress are analyzed to be the main mechanism in the laser damage. The combined experimental and theoretical work gives an insight into the change of surface damage and material failure behavior, hence broadens the potential applications of Ge sheets in areas of laser material manufacturing and laser processing.